Strategy for Utilizing Village Fund Budget to Alleviate Poverty towards Village SDGs in Taeng Village Gowa Regenecy - Mutmainna Mutmainna; Khaeratul Mar’ah; Leni Emilia Sadli (Ridwan Institute, 2023)
Based on the results of the National Socioeconomic Survey (Susenas) conducted by BPS, the number of poor people in September 2020 was 27.55 million people, an increase of 1.13 million people compared to March 2020 and an increase of 2.76 million people compared to September 2019. Rural areas in Indonesia still have more poor people than urban areas. This study was conducted to determine the strategy of using village funds in poverty alleviation in the Taeng Village area of Gowa District, to determine the effectiveness of using village funds for poverty alleviation in the Taeng Village area of Gowa District. This type of research is exploratory research using qualitative descriptive methods, attitudes and perceptions of people individually or in groups. The form of strategies carried out by the Taeng Village government through the village fund program empowers the community and reduces poverty, namely road and bridge infrastructure development, Women's Empowerment Training and Counseling. From the results of research in Taeng Village, Gowa Regency regarding the village fund budget as an effort to alleviate poverty towards SDG's Village, namely overcoming poverty, hunger and economic stability. Based on the results of the study, it can be concluded that the village fund budget has an impact on several informants, namely they feel helped by the village fund budget. It can be seen from the use of village funds spent to meet daily needs and village funds managed for entrepreneurship as additional income.